Green Economy: Green Innovation Strategy in Enhancing Sustainable Performance of MSMEs at Semarang City Through Competitive Advantage - Suci Ayu Sudari; Udriyah Udriyah (International Publisher, 2026)
This study aims to analyze the effect of green innovation on sustainable performance of MSMEs at Semarang City through competitive advantage. This study employs a deductive approach, in which the research begins with general theories and is then narrowed down into more specific hypotheses. The method used is quantitative, utilizing primary data as the research instrument. The sampling design uses non-probability sampling with a convenience sampling technique. Data testing includes descriptive analysis, hypothesis testing, and path analysis using the Structural Equation Model (SEM) method with SmartPLS 4. The findings indicate that green innovation has a significant effect on competitive advantage. Competitive advantage has a significant effect on sustainable performance. And there is an indirect effect, green innovation has a significant effect on sustainable performance through competitive advantage. MSMEs need to strengthen their business reputation through the implementation of environmentally friendly business practices. These efforts not only improve the company's image but also strengthen the MSME's competitive advantage and its impact on sustainable performance.